HADIS MENGENDALIKAN AMARAH DALAM PERSPEKTIF PSIKOLOGI - Rovi Husnaini (Diroyah : Jurnal Studi Ilmu Hadis, 2019)
Emotion for each individual has an important role in life. Humans are creatures created by Allah SWT who are equipped with emotions. In the view of psychology, human emotions are divided into two categories, namely, positive emotions and negative emotions. One of the negative emotions angry, the Prophet Muhammad SAW said "Not a strong person (the real) by (always defeating his opponent in) struggles (fights), but none other strong people (the actual) is able to control himself when angry" (HR. Bukhari No. 5763 & HR Muslim, No. 2609). Angry emotions are not to be arrested but the Prophet Muhammad (PBUH) advocated being controlled. The advice of the Prophet Muhammad in the hadith about controlling emotions of anger has harmony with psychology, in the perspective of psychology controlling anger can be through soft catharsis, rationalization, copying strategy. Emotional control has a positive impact on physical health, psychological, and in maintaining social interaction